Accessibility Based on User Perception of Rehabilitation Center for People with Physical Disabilities (BRSPDF) Wirajaya Makassar - Mutmainna - Mansyur; Triyatni Martosenjoyo; Edward Syarif (EPI International Journal of Engineering, 2021)
In planning a building and environment, not only design that needs to be considered but also accessibility. Accessibility that can be accessed by everyone for the creation of equal opportunities. In designing, the perception of the environment is important, The Social Rehabilitation Center for People with Physical Disabilities (BRSPDF) Wirajaya is a rehabilitation center for people with physical disabilities to acquire skills so that they can work independently. So accessibility is very important in supporting activities and smooth activities in the Hall. Based on this, this study aims to analyze the level of conformity of accessibility elements to the principle of facilities and accessibility. In this research the method used is the survey method and use the questionnaire as a research instrument, a type of quantitative detiptive research.. The results showed that the level of conformity of accessibility elements to safety is 74.1%, convenience 79.5%, usability 71.8%, and independence 64.1%.